Synthesis and Characterization of some new 2,5-disubstituted- 1,3,4-oxadiazole derivatives Containing Antipyrine moiety. - Rashid, Mohammad Amin Mohammad; MohammedMohammed, Sewara Jalal (Sulaimani Journal for Pure and Applied Sciences, 2016)
Some new 2,5-disubstituted-1,3,4-oxadiazolels of type (E)-4-((1-(5-(substitutedphenyl) 1,3,4-oxadiazol-2-yl)pro-1-en-2-yl)amino)-1,5-dimethyl-2-phenyl-1H-pyrazol-3(2H)- one were synthesized in (60-81%) yield under solvent free conditions using grinding technique through the reaction of hydrazide intermediate with benzaldehyde or different substituted benzaldehydes in the presence of catalytic amounts of iodine molecular as a single step. The structures of all the synthesized compounds were confirmed on the basis of their physical properties, IR, 1H-NMR and Mass spectral data.
Keywords: 4AminoantipyrineEthyl acetoacetateEnaminoneHydrazideOxadiazole derivatives